Recent developments in structural adjustment with special emphasis on compensatory policies: the case of Jamaica: country paper - Tyson, Sam (ILO. PREALC Caribbean Office Port of SpainTT, 1991)
Examines the background of compensatory policies introduced in Jamaica in relation to the structural adjustment programme. Assesses the impact of the broader programme and evaluates the compensatory measures adopted.